The New Role for an Old Kinase: Protein Kinase CK2 Regulates Metal Ion Transport - Adam J. Johnson; Ming J. Wu (MDPI AG, 2016)
The pleiotropic serine/threonine protein kinase CK2 was the first kinase discovered. It is renowned for its role in cell proliferation and anti-apoptosis. The complexity of this kinase is well reflected by the findings of past decades in terms of its heterotetrameric structure, subcellular location, constitutive activity and the extensive catalogue of substrates. With the advent of non-biased high-throughput functional genomics such as genome-wide deletion mutant screening, novel aspects of CK2 functionality have been revealed. Our recent discoveries using the model organism Saccharomyces cerevisiae and mammalian cells demonstrate that CK2 regulates metal toxicity. Extensive literature search reveals that there are few but elegant works on the role of CK2 in regulating the sodium and zinc channels. As both CK2 and metal ions are key players in cell biology and oncogenesis, understanding the details of CK2's regulation of metal ion homeostasis has a direct bearing on cancer research. In this review, we aim to garner the recent data and gain insights into the role of CK2 in metal ion transport.